Assessing the amenability of a free milling gold ore to coarse particle gangue rejection - McGrath, Teresa; Eksteen, Jacques; Bode, P. (Elsevier, 2018)
Coarse particle gangue rejection is highly topical due to the potential benefit in removing a significant fraction of gangue prior to fine grinding, thereby creating significant potential savings in energy, water, reagents (and consumables) and significantly reducing fine tailings deposition requirements. The research presented here focusses on characterising and evaluating liberation and separation of gangue from a gold bearing sulfide ore in the -2 mm +0.3 mm size range (associated with post tertiary crushing). This particle size range was chosen from a materials handling perspective, focussing on material that can be transported by pumping an ore slurry. This paper will review the procedure and results of an in-depth assessment of the amenability of a gold ore to gangue rejection in the pumpable size range. The liberation of the non-sulfide gangue of crushed gold ore is evaluated by proxy using sequential sink-float analysis for various size fractions. SPT (sodium polytungstate) and LST Fastfloat® (comprising of lithium heteropolytungstates) were used as heavy liquids. The results establish the deportment of gold to the sink and float products yielding a recovery versus mass pull relationship. Liberation patterns were investigated as produced by various crushing technologies such as vertical shaft impact (VSI) crushing, cone crushing, SelFrag®-based comminution, and high pressure grinding roll (HPGR) crushing. The gangue liberation behaviour, using a sink-float proxy, was dependent upon the mode of crushing and varied for different size intervals. The results of the Gangue Rejection Amenability Test allow for the determination of the grade and mass splits that are achievable for a given crushed product. The method is applicable to a wide range ores with varying mineralogies. Significant variation in the amount of barren rejectable gangue for a given gold ore and a given gold loss to rejects was observed for the various crushing technologies at the same 100% pass size, even though the particle size distributions were fairly similar.